1994
DOI: 10.1203/00006450-199401000-00021
|View full text |Cite
|
Sign up to set email alerts
|

Androgen-Receptor Blockade Enhances Pulsatile Luteinizing Hormone Production in Late Pubertal Males: Evidence for a Hypothalamic Site of Physiologic Androgen Feedback Action

Abstract: ABSTRACT. To determine potential mechanisms by and frequency of hypothalamic GnRH release in late puwhich androgens alter gonadotropin secretion and elimibertal boys. (Pediatr Res 35: 102-106,1994) nation in the pubertal male, we administered the potent nonsteroidal androgen receptor blocking agent, flutamide, to eight males with Tanner IV or V genital development.AbbreviationsVenous blood samples were obtained every 10 min for 24 GnRH, gonadotropin-releasing hormone h and assayed for LH by a sensitive and hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
1

Year Published

1996
1996
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(8 citation statements)
references
References 19 publications
0
7
0
1
Order By: Relevance
“…Variation to this extent was not observed in any other treatment group and may stem from the relatively low affinity of flutamide for the androgen receptor (Edelson, 1984;Simard, Luthy, Guay, Belanger, and Labrie, 1986), making it difficult to maintain a complete occupation of androgen receptors with flutamide. This is particularly problematic because blockade of the receptor with flutamide is also likely to remove negative feedback control of gonadotropin secretion (Veldhuis, Urban, and Dufau, 1992;Kerrigan, Veldhuis, and Rogol, 1994), increasing fetal T secretion. Under such conditions, any momentary reduction in the flutamide androgen receptor blockade would allow the larger pool of fetal T to interact with androgen receptors.…”
Section: Discussionmentioning
confidence: 99%
“…Variation to this extent was not observed in any other treatment group and may stem from the relatively low affinity of flutamide for the androgen receptor (Edelson, 1984;Simard, Luthy, Guay, Belanger, and Labrie, 1986), making it difficult to maintain a complete occupation of androgen receptors with flutamide. This is particularly problematic because blockade of the receptor with flutamide is also likely to remove negative feedback control of gonadotropin secretion (Veldhuis, Urban, and Dufau, 1992;Kerrigan, Veldhuis, and Rogol, 1994), increasing fetal T secretion. Under such conditions, any momentary reduction in the flutamide androgen receptor blockade would allow the larger pool of fetal T to interact with androgen receptors.…”
Section: Discussionmentioning
confidence: 99%
“…Androgens have been shown to regulate LH secretion negatively in late-pubertal boys [26], as well as in adult males [27]. Our observations suggest that androgens have a minor role compared with oestrogens in regulating LH as well as FSH secretion in early- and mid-pubertal boys.…”
Section: Discussionmentioning
confidence: 46%
“…Despite differences in experimental design, duration of androgen withdrawal, analytical methods, and the choice of volunteers/ patient populations, an earlier study also reported a hypoandrogenemia-stimulated increase in LH pulse frequency, albeit in primary hypogonadal men withdrawn for a longer interval from im testosterone ester replacement therapy (41). Likewise, increased LH pulse frequency occurs in men treated with an androgen receptor antagonist to impede testosterone's negative feedback actions (1,42,43). Conversely, slowing of LH pulse frequency results from infusions of pharmacological amounts of 5␣-reduced androgen (6).…”
Section: Discussionmentioning
confidence: 99%